THE ROLE OF ARTISTIC AND AESTHETIC EDUCATION OF PRESCHOOL CHILDREN IN MODERN CONDITIONS (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Artistic and aesthetic education of preschoolers is not just drawing and modeling, but a complex process of forming a harmoniously developed personality capable of creativity, emotional perception and self-expression. In the context of rapid technological progress and information saturation, the role of this education becomes especially significant. The influence of artistic activity on the development of communication skills, creative thinking, aesthetic taste and moral values ​​in children is considered. Modern approaches include integrative methods, project activities, gaming technologies and the use of digital resources.